Wisława Szymborska and ut pictura poesis - Weronika Szwedek (Проглас, 2021)
Wisława Szymborska is considered an artist in whose poetry the ekphrasis plays a key role. Szymborska wrote numerous works that fall into this context as a genre linking literature and the fine arts, and representing a literary description of a painting. Among Shimborska’s favorite artists are Vermeer, Rubens, Bruegel and Hiroshige Utagawa.